Modification of TPE using selected additives / Lim Chun Piao - Lim, Chun Piao (2009)
Blends of well characterized hydrogenated polystyrene-polybutadiene-polystyrene (SEBS) triblock and additives consisting tackifiers provide unique rubbery and glassy network interaction with controlled amounts of volume fraction (f) of certain phase. Such systems also provide quantitative information correlated from the concentrations of trapped chain entanglements in polymer additives blend. Two different resins (aliphatic type, Sukorez SU420 and aromatic type, Norsolene W85) were blended carefully in various amounts with a typical SEBS triblock copolymer (TSCR's Taipol 3152H) to form three series of samples for viscoelastic study. The unusual behaviours in dynamic mechanical properties suggest that complex morphology of gyroid exists in certain blending ratio. The mechanical properties of these blended materials were studied in sinusoidal oscillation of film tension mode at 1 Hz over a temperature range from room temperature to about 110°C. The effect of tackifier mixture on the mechanical properties depends upon their compatibility and concentration in the network, as well as partial interaction with other phase. It acts as a diluent, lowering the storage modulus in the rubbery region. Several unexpected mechanisms appeared as a result of suspected gyroid structure formation, and their existence resulted from certain critical volume fraction of components. The various mechanisms (chain architecture, morphology formation, chain topology) associated with the polystyrene chains have been incorporated from previous efforts whose parameters were given in terms of the structural and compositional features of complex morphology formation. The correlation in between compatibility, morphology and rheology properties successfully predicts the level and the location of the dynamic response for the various blends studied here.